Bladder calculi formed over a hair nidus in spinal injury cases. (May 2014) - Joshi, Mrinal; Mittal, Nimish
<x content-type="archive" xml:space="preserve">Abstract</x> Clean intermittent catheterization has been demonstrated to be a safe and effective method of bladder drainage in patients with neurogenic bladder dysfunction. However, breakdowns in technique may allow the introduction of foreign matter into the bladder and thereby result in bladder calculi. The three cases reported herein demonstrate this potential problem in persons with spinal cord injury (SCI) with hair nidus as the source of bladder calculi causing neurogenic bladder. In each situation, the problem was identified, calculi were removed cystoscopically and the patient and/or the ancillary aid were reinstructed. We recommend annual renal function tests, ultrasound and cytoscopic screening in high suspicion cases to allow early detection of bladder calculi in persons with SCI and prevent further urinary tract infections. This report also emphasizes the need for patient education and a careful follow-up preventing bladder calculi and thus, minimizing the morbidity in persons with SCI.